UAV-assited Wireless Powered Sensor Network over Rician Shadowed Fading Channels; Microwaves, Antennas, Communications and Electronic Systems (COMCAS) - Panich S. Stefan; Ponnimbaduge Perera T. D. Tarindu Dilshan; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Stefanovic C. Caslav; Prlincevic B. Bojan (2019, 2019)
Title screen